ANALISIS PENYUSUNAN LAPORAN KEUANGAN PADA KOPERASI SERBA USAHA PELITA KITA DI KABUPATEN KAPUAS HULU - Maghfiratul Fitriyani, Elqori; Dwi Widyastuti, Reni (Program Studi Akuntansi Universitas Panca Bhakti, 2023)
The Financial Statement is a part of the management's accountability report for an accountingperiod, which can be used as material for assessing the results of the work of the management of acompany. This study aims to find out whether the preparation of the financial reports of the Pelita KitaMulti-Business Cooperative in Kapuas Hulu Regency is in accordance with SAK ETAP. This researchapproach uses a qualitative descriptive approach. The purpose of using a qualitative descriptiveapproach is to be able to provide information that has no manipulative elements from the events thathave occurred. Based on the research results, the preparation of financial statements by the Pelita KitaMulti-Business Cooperative has not been based on SAK ETAP. The Pelita Kita Multi-BusinessCooperative only makes a Financial Statement of the Balance Sheet and Calculation of business results.According to SAK ETAP, complete financial statements consist of a balance sheet, profit and lossreport, statement of changes in equity, statement of cash flows and notes to financial statements.According to SAK ETAP on cooperatives, complete cooperative financial reports consist of balancesheets, calculation of operating results, reports of changes in equity, reports of cash flows and notes tofinancial statements.